Gender Biases Represented in Malaysian and Thai National Language Textbooks for Primary Schools - Mekhirunsiri, Pitchayada; Rajo Sathian, Mala (Jurnal Pengajian Media Malaysia, 2024)
This paper examines gender representations in language textbooks in Malaysia (Buku Teks Bahasa Melayu) and Thailand (Bhasapatee Chan Prathom Suksa) used at the primary school level, years 1–6. Despite their declared aims of teaching language skills, moral values and critical thinking, both textbooks embed gender biases shaped by their respective social and cultural contexts. We compared these textbooks qualitatively using discursive analytical techniques, and quantitatively by counting and categorizing the number of occurrences of biases. The comparison revealed both similarities and differences in how gender roles and stereotypes are presented. We found multiple instances supporting our assertion that both textbooks are gender-biased in many ways.